KARAKTERISTIK FISIKO-KIMIA JAMUR TIRAM PUTIH (Pleurotus ostreatus) SELAMA PENYIMPANAN - Ias Marroha Doli Siregar; Filli Pratama; Basuni Hamzah; Wulandari Wulandari (Jurnal Teknologi & Industri Hasil Pertanian, 2020)
White oyster mushroom is a type of food that is easily damaged (a highly perishable food). This study aimed to determine the rate of change in texture, color, volatile compounds, and amino acid composition in white oyster mushrooms during storage at various temperatures and CO2 concentrations. The research design used was a Factorial Complete Randomized Design (FCRD), with a storage temperature treatment (A) consisting of three levels, namely A1 (10 ± 2 °C), A2 (20 ± 2 °C), A3 (30 ± 2 °C) and treatment of adding CO2 gas (B) consisting of four levels, namely B0 (control), B1 (20%), B2 (30%), and B3 (40%). Tukey HSD carried out the treatment that was significantly different at a 5% level. The results showed that the order of the quality decline reaction of the white oyster mushrooms was order one. The best treatment for storing the white oyster mushrooms with a MAP method of PE packaging was the addition of 30% CO2 at a storage temperature of 10 °C. The major volatile compounds in fresh white oyster mushrooms were 3-Octanone (44.54%), 3-Octanol (23.24%), 3-Heptanone, 6-methyl- (10.26%), whereas after 10 days of storage were 3-Octanone (35.05%), 3-Octanol (25.89%), and 5-Ethyl-3methylhept-1-en-4-ol (8.45 ppm). The major amino acid composition in fresh white oyster mushrooms was glutamate, aspartate, and lysine, whereas after 10 days of storage were glutamate, lysine, and aspartate.Keywords : Amoni acid, White oyster mushroom